OS9.8 Genomic landscape of medulloblastoma in adults. (6th September 2019) - Goschzik, T; zur Mühlen, A; Dörner, E; Waha, A; Friedrich, C; Hau, P; Pietsch, T
Abstract: BACKGROUND: Medulloblastoma (MB) is a rare disease in adults. Therefore, only few cohorts have been studied so far. METHODS: Histological features were evaluated and annotation of the tumors to WNT-MB, SHH-MB, and non-WNT/non-SHH-MB was performed by immunohistochemistry. Systematic analysis of tumor samples for genome-wide copy alterations was done by molecular inversion probe array. WNT- and SHH-activated MB were screened by NGS panel and Sanger sequencing for known MB-related genes. RESULTS: The cohort of tumors from 117 patients contained 14.5% WNT-MB, 63.2% SHH-MB, and 22.2% non-WNT/non-SHH MB. Classic histology was found in WNT-MB, non-WNT/non-SHH-MB and 22% of SHH-MB; 78% of SHH-MB showed desmoplastic/nodular histology. In WNT-MB, CTNNB1 mutations were found in 88.2% and monosomy 6 in 52.9% of cases. In SHH-MB, PTCH1 mutations were present in 40% of cases and chromosome 9q loss including the PTCH1 locus was the most frequent copy number event in SHH-MB (50%), while SMO and SUFU mutations were found only in 15.4% resp. 7.7%. Mutations in the TERT promoter region were found in 92.3% of SHH-MBs. Only 2 (3%) of the SHH-MB were TP53 -mutated (1.7% of the whole cohort). In non-WNT/non-SHH-MB, isochromosome 17q was the most frequent chromosomal alteration (84.6%). A previously published whole chromosomal aberration (WCA) signature with ≥1 WCA was found in 69.2% of cases. For 85 cases, survival data were available. WNT-MB presented no relapses (5-year OS: 100%), while SHH-MB with wildtype TP53 and non-WNT/non-SHH-MB showed similar outcomes (5-year OS: 78.1% and 69.1%, respectively). Both SHH-MB patients with mutant TP53 died of disease. Patients with non-WNT/non-SHH-MB characterized by the cytogenetic WCA phenotype showed - as described in pediatric standard-risk MB - significant better overall survival compared to patients with tumors lacking any WCA (p=0.01). CONCLUSIONS: Adult MB represent four defined biological/genomic entities. In contrast to previously published data adult patients with WNT-MBs showed excellent survival. However, the number of patients with WNT-MB was limited so that this result has to be interpreted with caution. While in our cohort SHH-MB- TP53 wt were standard risk independent of their mutational or chromosomal status, non-WNT/non-SHH-MB patients could be divided into two risk-groups according to the presence or absence of WCA in the tumors as previously published for childhood standard-risk MB by our group.